2022
DOI: 10.5468/ogs.21345
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive pregabalin for postoperative analgesia during minimally invasive hysterectomy: a systematic review and meta-analysis of randomized controlled trials

Abstract: We aimed to perform a systematic review and meta-analysis of all randomized placebo-controlled trials (RCTs) that examined the analgesic benefits of preemptive pregabalin among patients undergoing minimally invasive hysterectomy. Five major databases were systematically screened until August 29, 2021.Relevant studies were evaluated for risk of bias. Endpoints were analyzed using the random-effects model and pooled as the mean difference or risk ratio with a 95% confidence interval. Four studies with seven trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In a study conducted by Kohli A systematic review and meta-analysis of randomised clinical trials evaluating the preemptive use of pregabalin in minimally invasive hysterectomy surgeries demonstrated similar results to our study; patients in the intervention group had lower postoperative pain scores and less opioid consumption. 25 In a meta-analysis of 24,682 patients, gabapentinoids were shown to reduce acute postoperative pain intensity at 6, 12, 24, and 48 h and were associated with lower opioid consumption. However, the authors reported that there was no clinical significance, since the observed effects were small.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Kohli A systematic review and meta-analysis of randomised clinical trials evaluating the preemptive use of pregabalin in minimally invasive hysterectomy surgeries demonstrated similar results to our study; patients in the intervention group had lower postoperative pain scores and less opioid consumption. 25 In a meta-analysis of 24,682 patients, gabapentinoids were shown to reduce acute postoperative pain intensity at 6, 12, 24, and 48 h and were associated with lower opioid consumption. However, the authors reported that there was no clinical significance, since the observed effects were small.…”
Section: Discussionmentioning
confidence: 99%